Nanocrystalline hydroxyapatite intervertebral cages induce fusion after anterior cervical discectomy and may be a safe alternative to PEEK or carbon fiber intervertebral cages. (1st November 2016) - Timothy, Jake; Wilson, Jamie; Rice, Edward; Hall, Richard
Abstract: Purpose : Nanocrystalline hydroxyapatite (nHA) cages have emerged as a new alternative to carbon fiber or polyether ether ketone (PEEK) devices to promote intervertebral fusion. No evidence has been published to date regarding rates of fusion for these devices after anterior cervical discectomy and fusion (ACDF).Methods : Eight patients underwent one- or two-level ACDF with nHA intervertebral cages (Nanoss ® -Cervical, Pioneer ® Surgical Technology, Inc., Marquette, MI). Radiographs, neck disability index (NDI) and visual analog scores (VAS) for pain were taken preoperatively and at a minimum of 19 months postoperatively.Results : At an average follow-up of 21 months, all eight patients (100%) achieved fusion as assessed by plain radiographs. Reduction in preoperative symptomology was comparable to previously published data with a mean reduction of neck VAS of 3, arm VAS of 6 and NDI reduced by 27%. Radiographs showed clear evidence of bridging bone.Conclusions : This series provides evidence that nHA intervertebral cages can successfully promote fusion after ACDF and may provide an alternative to carbon fiber and PEEK cages.